Proposta de modelo construtivo em wood frame: bamboo frame no Brasil - Oliveira, Diego Rodrigues de [UNESP]; Páschoa, Gláucia Pontes [UNESP]; Santos, Victor Galvão dos [UNESP]; Rosolem, Larissa Almeida [UNESP]; Silva, Gisela Carolina Neves da [UNESP]; Barbosa, Juliana Cortez [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Wood Frame constructive system is largely used and mainly spread over the developed countries. Because of the high quantity of bamboo in Asia, it was created a very peculiar constructive system over there named Bamboo Frame; which uses bamboo with structural function as stud. Therefore, the objective of this work is to create a constructive model using bamboo as stud to evaluate the execution process, potential use as low cost construction, and to make possible some future studies. The proposed model has de following dimensions: 48in (1,22m) length, 48in (1,22m) width, and 96in (2,44m) height. And 5 parts compound it: 1 window wall, 1 door wall, 2 sides wall, and 1 floor framing. The raw materials passed through machining processes in the Sawmill, and the execution and assembling of the wall were performed in the Furniture lab, at Campus Experimental de Itapeva – Unesp. We can conclude that the Bamboo Frame constructive model is very simple and easy to assemble; however, it’s necessary some special attention to set the bamboo studs, because of theirs thin walls. In addition, the use of a pneumatic nail gun makes the process easier.

O sistema construtivo Wood Frame é um sistema construtivo bastante empregado e difundido principalmente em países desenvolvidos. Devido a grande abundância de bambu na Ásia, foi desenvolvido um sistema construtivo bastante peculiar chamado Bamboo Frame, o qual utiliza bambu com a função estrutural de montantes. Assim sendo, este trabalho teve como objetivo a elaboração de um modelo construtivo em Bamboo Frame para analisar o seu processo de execução, uso em construções populares e futuramente realizar ensaios diversos. O modelo proposto possui dimensões de 48in (1,22m) de comprimento por 48in (1,22m) de largura e 96in (2,44m) de altura, e é composto por 5 partes: 1 parede com janela, 1 parede com porta, 2 paredes laterais, e 1 base. O material foi usinado na Serraria e a montagem e execução das paredes foi realizado no laboratório de Mobiliário, no Campus Experimental de Itapeva. E pode-se concluir que o modelo construtivo Bamboo Frame é bastante simples, sendo necessário maior atenção na fixação dos montantes de bambus, devido as suas paredes delgadas. E a utilização do pinador pneumático torna o processo extremamente eficiente.
Keywords: Wood; Bamboo; Construction; Madeira; Bambu; Construção